2014
DOI: 10.1371/journal.pone.0095564
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic HMOX1 Expression Positively Correlates with Bach-1 and miR-122 in Patients with HCV Mono and HIV/HCV Coinfection

Abstract: AimTo analyze the expression of HMOX1 and miR-122 in liver biopsy samples obtained from HCV mono-and HIV/HCV co-infected patients in relation to selected clinical parameters, histological examination and IL-28B polymorphism as well as to determine whether HMOX1 expression is dependent on Bach-1.Materials and MethodsThe study group consisted of 90 patients with CHC: 69 with HCV mono and 21 with HIV/HCV co-infection. RT-PCR was used in the analysis of HMOX1, Bach-1 and miR-122 expression in liver biopsy samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These findings are consistent with an immune-modulatory role for HO-1 in HIV-1 infection. Additionally, HIV/HCV-coinfected individuals have lower liver HO-1 expression than that observed in HCV-monoinfected individuals; this loss of liver HO-1 is particularly evident in subjects with high HIV loads and low CD4 ϩ T lymphocyte counts (44). These findings, in conjunction with our observation of HO-1 deficiency in brain tissue from HIV-infected subjects, suggest that HIV infection modulates HO-1 expression in the CNS and in peripheral tissues (3).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These findings are consistent with an immune-modulatory role for HO-1 in HIV-1 infection. Additionally, HIV/HCV-coinfected individuals have lower liver HO-1 expression than that observed in HCV-monoinfected individuals; this loss of liver HO-1 is particularly evident in subjects with high HIV loads and low CD4 ϩ T lymphocyte counts (44). These findings, in conjunction with our observation of HO-1 deficiency in brain tissue from HIV-infected subjects, suggest that HIV infection modulates HO-1 expression in the CNS and in peripheral tissues (3).…”
Section: Discussionsupporting
confidence: 56%
“…An antiviral effect of HO-1 induction has been observed in infection studies of hepatitis C virus (HCV) (36), hepatitis B virus (HBV) (37), Ebola virus (38), enterovirus 71 (EV71) (39), vaccinia virus (40), and porcine reproductive and respiratory syndrome virus (41). Interestingly, HCV has been reported to downregulate HO-1 protein expression (42,43), although contrasting studies report HO-1 induction by HCV (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…It plays crucial role in suppressing inflammation and protecting against oxidative stress. Upregulation of HMOX-1 is an indication of oxidative stress [ 33 ]. We have previously shown that Nef expression in monocytic cells induces the expression of proinflammatory cytokines and thus acts like a cellular stress signal.…”
Section: Discussionmentioning
confidence: 99%
“… 68 In addition, higher HMOX1 expression was correlated with higher expression of Bach1 and miR-122 in chronic HCV patients. 69 Several miRNA profiling studies have demonstrated alterations in miRNAs expression and identified miRNA-mRNA regulatory networks during HCV infection. 51 , 70 , 71 , 72 Differential upregulation of hsa-miR-130a, hsa-miR-130b, hsa-miR-298, hsa-miR-193a-5p and hsa-miR-371-5p were observed in HCV Con1 replicon in comparison to control cells.…”
Section: Cellular Mirnas In Hcv Mediated Liver Disease Progressionmentioning
confidence: 99%